The nature of sports marketing - André Bühler; Gerd Nufer; Carsten Rennhak (Hochschule Reutlingen, School of International Business (SIB), 2006)
Sports marketing has established itself over the last three decades not only as a very special form of marketing but also as an own subject of research. However, it is quite surprising that the nature of sports marketing is relatively unknown as different definitions of sports market-ing indicate. Indeed, a generally accepted definition does not exist to date and opinions about the nature of sports marketing differ widely. This paper examines the nature of sports market-ing and therefore seeks to contribute to the ongoing discussion as to whether sports marketing is any different from principal marketing or just a modified version. It starts with a discussion of three different definitions of sports marketing. Then the unique characteristics of sports and sports marketing are described followed by implications for sporting organisation, companies involved in sports marketing and sports marketing academics. The paper concludes with a summarizing concept of sports marketing that illustrates the very special nature of sports marketing both verbally and graphically.
urn:nbn:de:bsz:21-opus-31574
Keywords: 650